Istihsan Concept in Multi Contract Online Transactions of Go-Food Services in The Go-Jek Application - Lusiana, Lusiana; Harun, Muhammad; Fauziah, Fauziah; Abdillah, Muhammad (Nurani, 2022)
Technological developments are very influential on the lives of the world's people, one of which is used for business purposes or known as Electronic Commerce (E-Commerce). Several E-Commerce facilities such as online transportation, online payments, online shopping, are practical facilities that are in great demand by the public. As an online food delivery service known as Go-Food. Go-Food application transactions or food orders have several contracts (multi-contract). This research is a field research. The data collected is analyzed descriptively qualitatively, that is, describes as clearly as possible the related data, then concluded deductively, that is, draws conclusions from statements that are general to specific. So that understanding the research results can be easily understood and understood. Some of the contracts in Go-Food transactions are as follows: PT. Go-Jek and merchants. PT. Go-Jek with merchants is an ijarah agreement. Transactions between Pt. Go-Jek and Driver, a collaboration between Go-Jek and drivers and known as the cooperation system (Syirkah). Contract between the consumer and the driver, if the consumer makes a payment using his own go-pay system, the transaction that occurs between the two is buying and selling, but if it is in cash, then there is a wakalah contract, here it will also be a qardh contract because the consumer owes it to the driver. Contracts between drivers and merchants, there are buying and selling activities between drivers and merchants, buying and selling represented by the driver to the merchant, representative transactions like this in Islamic law are known as wakalah contracts. With the istihsan method, economic activities that provide convenience and good benefits without harm and injustice to mankind can be answered and proven by the istihsan method, so that sharia economic activities can always exist and can compete with conventional economics.